Ambiente educativo clínico al final del internado en la Escuela de Medicina de la Universidad de Chile: resultados de la encuesta PHEEM - Vásquez D., Nicole; Peralta C., José (Revista Hospital Clínico Universidad de Chile, 2013)
Introduction: The educational commitment is an obligation of educational institutions. For this, we must look determinants of achievement in undergraduate, as the educational environment, defined as “the most important manifestation and conceptualization of the curriculum”. Objective: To describe the perception of the educational environment in boarding Hospital Gynecology and Obstetrics, Internal Medicine, Pediatrics and Surgery. Methods: Cross-sectional study using the survey PHEEM 2012 to 164 graduates, for internship and campus. Determination of differences by campus or internship, calculating partition coefficient of variance and including survey, internship and campus. Results: The overall score was 103.70 ± 42.38, corresponding to “an educational environment more positive than negative, with room for improvement.” The interpretation by dimensions of Autonomy, Perceived Social Support teaching and was “more positive than negative”, “headed in the right direction” and “more pros than cons” respectively. No major differences in the breakdown by campus and interned. Conclusion: The Medical School of the University is situated very close to other national and international institutions with student-centered curriculum. Measure and analyze these results permanently will assess the impact of changes in clinical practice and curricular innovation processes.